Informal organization in innovative teams: A comparative case study (2016)
This article presents a comparative, mixed, transversal and descriptive study based on a multilevel model of psychosocial factors to identify, evaluate and comprehend the dynamics of the informal organization in company innovation. The research is done at a team level through the application of the model instruments. Teams, for comparison purposes, are classified as “innovative” and “non-innovative” based on their practice of innovative activities as recognized by the Organization for Economic Co-operation and Development (OECD). Due to the non-parametric distribution of variables, the statistics Test U of Mann Whitney is used to identify the differences. The sample corresponds to 70 teams, formed by 563 people from 21 companies. The study finds there are differences in the factors of cohesion, potency and learning climate between the teams that do innovation activities and those which do not, as well as differences in the leadership factors between teams that do Research and Development activities and those which do other types of innovation activities. A comparative multi-case between four “innovative” teams from two companies is developed to better understand the relationship of these factors with innovation. The results provide evidence of the relationship existing between the cultural factors and the psychosocial factors of potency and learning climate.